Dissecting the effects of antibiotics on horizontal gene transfer: Analysis suggests a critical role of selection dynamics. (4th October 2016) - Lopatkin, Allison J.; Sysoeva, Tatyana A.; You, Lingchong
Abstract : Horizontal gene transfer (HGT) is a major mechanism responsible for the spread of antibiotic resistance. Conversely, it is often assumed that antibiotics promote HGT. Careful dissection of the literature, however, suggests a lack of conclusive evidence supporting this notion in general. This is largely due to the lack of well‐defined quantitative experiments to address this question in an unambiguous manner. In this review, we discuss the extent to which HGT is responsible for the spread of antibiotic resistance and examine what is known about the effect of antibiotics on the HGT dynamics. We focus on conjugation, which is the dominant mode of HGT responsible for spreading antibiotic resistance on the global scale. Our analysis reveals a need to design experiments to quantify HGT in such a way to facilitate rigorous data interpretation. Such measurements are critical for developing novel strategies to combat resistance spread through HGT. Abstract : Horizontal gene transfer (HGT) is a major mechanism responsible for the spread of antibiotic resistance. Antibiotics can influence HGT dynamics by modulating the gene transfer rate, acting as a selection force, or both. Decoupling these factors is critical to determine the extent that antibiotics influence HGT.